COMPARATIVE ANALYSIS OF THE CONCEPTS ‘‘CULTURE OF READING’’ AND ‘‘READING COMPETENCE’’ IN PEDAGOGICAL SCIENCES - Bektursinova, Gulkhumar Zholdasbaevna (SCIENCE and SOCIETY, 2026)
This article provides a comparative analysis of the essence, interconnectedness, and specific characteristics of the concepts "reading culture" and "reading competence," which hold a significant place in the system of pedagogical sciences. The author highlights the theoretical and methodological foundations of both concepts, defining their role in personal development and the educational process. The study demonstrates that while "reading culture" is a comprehensive socio-cultural phenomenon, "reading competence" is a pedagogical category focused on specific practical skills and outcomes. Concluding recommendations for their development are also presented.
Keywords: culture of reading; reading competence; pedagogical analysis; comparative approach; reading skills; text comprehension; educational system; personal development